Successfully Implementing Technical and Vocational Education and Training Programmes in Secondary Schools - Mitchell, Brendan; Buntic, Clare Gordon (World Journal of Vocational Education and Training, 2022)
Technical and vocational education and training (TVET) plays a critical role in developing essential labour market skills. While the original goal of TVET, which is still prominent today, was to prepare youth to enter the workforce by training them to be work ready, the global technological revolution and innovations in science and technology demands higher levels of education and technological skills for the 21st century. TVET has evolved to meet the needs of industry and countries. Strengthening technical and vocational education at the secondary education level provides a wider transformational vision for students to have the opportunity to gain these skills. There are challenges, which are more prevalent in some countries than others. For example, perception and participation in TVET has traditionally been stigmatized in favour of white-collar jobs. Additional challenges include contemporary curriculum and facilities, training and development of staff, and financial strains, which many developing nations have. This article sets out to provide information and guidance on the implementation of TVET programmes and focuses on: strong or emerging global TVET practice, with a focus on the secondary school sector; key features of successful practice, in order to extract the most relevant lessons; and the most common global challenges in developing successful TVET programmes, and how these can be addressed. While the article focuses on secondary education it contextualises this within the wider TVET and vocational education systems.